Scintigraphic Tracking of Allogeneic Mesenchymal Stem Cells in the Distal Limb After Intra‐Arterial Injection in Standing Horses. Issue 5 (1st June 2016) - Espinosa, Pablo; Spriet, Mathieu; Sole, Albert; Walker, Naomi J.; Vaughan, Betsy; Galuppo, Larry D.
Abstract : Objective: To assess the feasibility of intra‐arterial administration of allogeneic mesenchymal stem cells (MSC) in the median artery of standing horses and evaluate the distribution and retention of radiolabeled cells. Study Design: In vivo experimental study. Animals: Six research horses. Methods: Technetium 99m ‐HexaMethyl‐Propylene‐Amine Oxime‐labeled MSC were injected under ultrasound guidance in the median artery of 6 front limbs of 3 horses, standing under sedation. Scintigraphic images were obtained at the time of injection, and at 1, 6, and 24 hours postinjection. Six additional limbs from 3 horses were similarly injected with unlabeled MSC. Ultrasound was performed the following day for assessment of vascular changes. Results: Intra‐arterial injection was performed successfully in 11 of 12 limbs. In 1 limb, partial periarterial injection compromised the success of the procedure. Homogeneous distribution of radiolabeled MSC was observed through the entire distal limb, including within the hoof. Partial venous thrombosis was found in both groups of horses, but was subjectively less severe in horses injected with unlabeled MSC. No lameness was observed. Transient swelling of the distal limb occurred in only 1 limb. Conclusion: Intra‐arterial injection of MSC can be performed in standing horses under sedation and successfully distribute MSC to the distal limb. A risk of periarterial injection was identified but can be reduced with proper sedation, local anesthesia, and increased experience. Partial venous thrombosis was observed as a complication, but did not cause changes of clinical importance, other than rare transient swelling.